The Anti-Microbial Peptide (Lin-SB056-1)2-K Reduces Pro-Inflammatory Cytokine Release through Interaction with Pseudomonas aeruginosa Lipopolysaccharide - Lucia Grassi; Arianna Pompilio; Esingül Kaya; Andrea C. Rinaldi; Enrico Sanjust; Giuseppantonio Maisetta; Aurélie Crabbé; Giovanni Di Bonaventura; Giovanna Batoni; Semih Esin (MDPI AG, 2020)
The ability of many anti-microbial peptides (AMPs) to modulate the host immune response has highlighted their possible therapeutic use to reduce uncontrolled inflammation during chronic infections. In the present study, we examined the anti-inflammatory potential of the semi-synthetic peptide lin-SB056-1 and its dendrimeric derivative (lin-SB056-1)2-K, which were previously found to have anti-microbial activity against Pseudomonas aeruginosa in in vivo-like models mimicking the challenging environment of chronically infected lungs (i.e., artificial sputum medium and 3-D lung mucosa model). The dendrimeric derivative exerted a stronger anti-inflammatory activity than its monomeric counterpart towards lung epithelial- and macrophage-cell lines stimulated with P. aeruginosa lipopolysaccharide (LPS), based on a marked decrease (up to 80%) in the LPS-induced production of different pro-inflammatory cytokines (i.e., IL-1β, IL-6 and IL-8). Accordingly, (lin-SB056-1)2-K exhibited a stronger LPS-binding affinity than its monomeric counterpart, thereby suggesting a role of peptide/LPS neutralizing interactions in the observed anti-inflammatory effect. Along with the anti-bacterial and anti-biofilm properties, the anti-inflammatory activity of (lin-SB056-1)2-K broadens its therapeutic potential in the context of chronic (biofilm-associated) infections.